The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26196073
|View full text |Cite
|
Sign up to set email alerts
|

Cissus subtetragona Planch. Ameliorates Inflammatory Responses in LPS-induced Macrophages, HCl/EtOH-induced Gastritis, and LPS-induced Lung Injury via Attenuation of Src and TAK1

Abstract: Several Cissus species have been used and reported to possess medicinal benefits. However, the anti-inflammatory mechanisms of Cissus subtetragona have not been described. In this study, we examined the potential anti-inflammatory effects of C. subtetragona ethanol extract (Cs-EE) in vitro and in vivo, and investigated its molecular mechanism as well as its flavonoid content. Lipopolysaccharide (LPS)-induced macrophage-like RAW264.7 cells and primary macrophages as well as LPS-induced acute lung injury (ALI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Medicinal plants with natural sources still offer promising options and are recognized as therapeutic agents. In addition, understanding the mechanisms of therapeutic action could lead to the discovery of new drugs from natural sources with reduced or no side effects [ 21 , 22 , 23 ]. The edible freshwater green algae, P. japonica , has been described to possess pharmacological benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medicinal plants with natural sources still offer promising options and are recognized as therapeutic agents. In addition, understanding the mechanisms of therapeutic action could lead to the discovery of new drugs from natural sources with reduced or no side effects [ 21 , 22 , 23 ]. The edible freshwater green algae, P. japonica , has been described to possess pharmacological benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening these findings, immunoblot analyses of the level of phosphorylation of AP-1 subunits, c-jun and c-Fos, revealed that Pj-EE-CF modulates the transcriptional activation of AP-1. Previous studies reported the essential role and mechanism of MAPKs in activating AP-1 pathways [ 7 , 23 , 25 ]. Consequently, we checked signaling molecules upstream of this AP-1 activation, and Pj-EE-CF specifically inhibited ERK and p38 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bands were documented, and band intensity was measured using ImageJ software. For preparing lung lysate samples, the upper lobes of the right lungs of the mice used in the ALI experiment (see below) were collected, frozen in liquid nitrogen, and stored at −80 • C. The tissues were thawed and homogenized, and whole protein lysates were prepared as previously described [68].…”
Section: Luciferase Reporter Gene Assaymentioning
confidence: 99%
“…To perform the LC-MS/MS analysis, Xevo G2-XS Q-TOF-LC/MS (Waters, Milford, MA, USA) was used as reported previously [33]. A reverse-phase BEH C18, 2.1 × 100 mm, 1.7 µm column (Waters, Milford, MA, USA) was used for UPLC.…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms)mentioning
confidence: 99%